The international debt crisis and the Craxi report - FORTE, F. (PSL Quarterly Review, 2013)
The United Nation's 'External Debt Crisis and Development' report, also known as the Craxi Report, can influence reformulation of debt-payment schemes of debtor nations. Concessions from lending nations and institutions can actually make debt securities more valuable by increasing the capacity of borrowing nations to pay. Recommendations on segmenting debtor nations into low-income, middle-income and 'middle-income developing' countries are discussed. Distinctions between the borrower countries can facilitate dealing with lending institutions when negotiating for debt payment and reduction schemes and added financing. JEL: F34, G01